Microbial reduction of CO2 from injected NaH13CO3 with degradation of n-hexadecane in the enrichment culture derived from a petroleum reservoir. (February 2018) - Ma, Lei; Liang, Bo; Wang, Li-Ying; Zhou, Lei; Mbadinga, Serge Maurice; Gu, Ji-Dong; Mu, Bo-Zhong
Abstract: Carbon capture and storage in deep subsurface oil reservoirs followed by subsequent microbial energy reconversion is a potentially new strategy for mitigating global warming and enhanced energy recovery simultaneously. However, our knowledge on the fate of CO2 and microbial community in response to CO2 injection is very limited. In the current study, microcosms containing both NaH 13 CO3 -injected and n -hexadecane amended were established with inoculum of a long-term alkane-degrading microbial consortium. Enhanced and accelerated methane production was observed in the bicarbonate-injected treatments. The isotope data showed that injected bicarbonate was transformed to methane by hydrogenotrophic methanogenesis. The composition of microbial community shifted in response to bicarbonate addition. Competitive Methanoculleus spp. and Methanobacterium spp. became dominant and potentially major contributors to methane production in response to bicarbonate injected and non-injected treatments. At the same time, injection of bicarbonate was associated with a decrease of Anaerolineaceae, but no obvious influence on Thermodesulfovibrio spp. known as the crucial players with potential role in the initial activation and intermediate metabolism, and thus inhibition on initial activation of alkane via fumarate addition mechanism characterized by the existence of assA genes by bicarbonate addition. The results present further promising insights into new technology to enhance microbial energy generation from carbon dioxide capture and storage. Graphical abstract: Highlights: Accelerated methanogenesis achieved with bicarbonate injection. Methanoculleus spp. dominated and methane production via hydrogenotrophic methanogenesis in bicarbonate-injected cultures. Promising energy regeneration from carbon dioxide is likely on industrial scale.